2013
DOI: 10.3174/ajnr.a3756
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Water Diffusion Changes in Primary Sjogren Syndrome

Abstract: BACKGROUND AND PURPOSE:Histopathologic studies have demonstrated WM damage in primary Sjögren syndrome. The purpose of this study was to evaluate WM microstructural changes by use of DTI-derived parameters in patients with primary Sjögren syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
(70 reference statements)
2
16
1
Order By: Relevance
“…One of these cases had Sjögren's syndrome, like our patient,3 but not the other two 24. In addition, although some studies have found cerebral white-matter lesions in Sjögren's syndrome,67 leukodystrophy-like white-matter changes have not been reported previously. Given that two of the three reported NMOSD cases were not associated with Sjögren's syndrome and leukodystrophy-like white-matter lesions in Sjögren's syndrome alone were not previously reported, the brain lesions of our patient were more likely to be related to current NMOSD than Sjögren's syndrome.…”
contrasting
confidence: 52%
“…One of these cases had Sjögren's syndrome, like our patient,3 but not the other two 24. In addition, although some studies have found cerebral white-matter lesions in Sjögren's syndrome,67 leukodystrophy-like white-matter changes have not been reported previously. Given that two of the three reported NMOSD cases were not associated with Sjögren's syndrome and leukodystrophy-like white-matter lesions in Sjögren's syndrome alone were not previously reported, the brain lesions of our patient were more likely to be related to current NMOSD than Sjögren's syndrome.…”
contrasting
confidence: 52%
“…Studies of other inflammatory autoimmune diseases show a similar pattern of findings, for example, in Sjögren Syndrome ( n =19; method = TBSS) there was increased MD and decreased FA in several tracts compared to controls. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In a small study of asymptomatic SS patients, white matter lesions were found in a higher burden than in age-matched controls, with multiple white matter tracts involved including the corticospinal tracts, superior longitudinal fasciculus, the anterior thalamic radiation, the inferior frontooccipital fasciculus, the uncinate fasciculus, and the inferior longitudinal fasciculus. 40 Historically, SS was thought to be a potential cause of relapsing-remitting symptoms in patients presenting with demyelinating appearing lesions in the brain, optic nerves, and/or spinal cord. Now, with the recognition of neuromyelitis optica spectrum disorders (NMOSD; discussed in article Autoimmune Neurologic Diseases in Children), it is likely that many of these SS patients in fact had underlying aquaporin-4 (AQP4) antibodies.…”
Section: Sjögren's Syndromementioning
confidence: 99%